2021
DOI: 10.1371/journal.pone.0248780
|View full text |Cite
|
Sign up to set email alerts
|

Predicting replicability—Analysis of survey and prediction market data from large-scale forecasting projects

Abstract: The reproducibility of published research has become an important topic in science policy. A number of large-scale replication projects have been conducted to gauge the overall reproducibility in specific academic fields. Here, we present an analysis of data from four studies which sought to forecast the outcomes of replication projects in the social and behavioural sciences, using human experts who participated in prediction markets and answered surveys. Because the number of findings replicated and predicted… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 46 publications
2
25
0
Order By: Relevance
“…The correlation between prediction market beliefs and replication outcomes was 0.42 (RPP), 0.30 (EERP), 0.84 (SSRP) and 0.76 (ML2) in these four studies. If we carry out a power calculation for the average correlation of 0.58 of these four studies (as reported in [ 13 ]) on replication outcomes for the first and third primary hypotheses below, we have 51% power to detect a correlation of 0.58 at the 0.005 level for ‘statistical significance’ and 83% power at the 0.05 level for ‘suggestive evidence’. In another project (the crowdsourcing a hypothesis test (CAHT) project [ 20 ]) we used an incentivized survey to predict effect sizes for new studies and we observed a correlation of 0.71 between predicted and observed effect sizes; this previous result is relevant as a meter of comparison for the second and fourth primary hypotheses below.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The correlation between prediction market beliefs and replication outcomes was 0.42 (RPP), 0.30 (EERP), 0.84 (SSRP) and 0.76 (ML2) in these four studies. If we carry out a power calculation for the average correlation of 0.58 of these four studies (as reported in [ 13 ]) on replication outcomes for the first and third primary hypotheses below, we have 51% power to detect a correlation of 0.58 at the 0.005 level for ‘statistical significance’ and 83% power at the 0.05 level for ‘suggestive evidence’. In another project (the crowdsourcing a hypothesis test (CAHT) project [ 20 ]) we used an incentivized survey to predict effect sizes for new studies and we observed a correlation of 0.71 between predicted and observed effect sizes; this previous result is relevant as a meter of comparison for the second and fourth primary hypotheses below.…”
Section: Methodsmentioning
confidence: 99%
“…As reported in Gordon et al . [ 13 ], pooling the results from four prediction market studies on binary outcomes (whether the study replicated or not; table 1 ) gives a 73% (76/104) correct prediction rate if we interpret prices above 50 as market prediction for successful replication. The corresponding number for a survey measure similar to the one we use here is 66% (68/103).…”
Section: Introductionmentioning
confidence: 99%
“…have made use of prediction markets [38][39][40] which have been shown to be one of the best methods for predicting replicability, although they are quite costly and time consuming to run. Both approaches show enormous potential to advance reproducibility efforts.…”
Section: Science-by-volume Approach To Advance the Neurosciencesmentioning
confidence: 99%
“…Given the challenges and significant resources required to run high-powered replication studies, researchers have sought other approaches to assess confidence in published claims and have looked to creative assembly of expert judgement as one opportunity. Initial evidence has supported the promise of prediction markets in this context (Dreber et al 2015;Camerer et al 2016Camerer et al , 2018Forsell et al 2019;Gordon et al 2020Gordon et al , 2021. However, practical deployment of prediction markets to evaluate scientific findings is also limited.…”
Section: Introductionmentioning
confidence: 99%